PEMODELAN APLIKASI UNIT KEGIATAN MAHASISWA (UKM) UNIVERSITAS SAHID SURAKARTA - Al Haris, Firdhaus Hari Saputro; Anwariningsih, Sri Huning; Barid, Aziz Jihadian (JURNAL GAUNG INFORMATIKA, 2015)
The development of information systems has a lot of influence on human life and is necessary for data processing facilities to obtain information quickly, precisely, andaccurately. The purpose of this research is to apliction modelling a UKM information system based on the website of Sahid Surakarta University can be accessed via theinternet with ease.The research method used of UKM at the University of Sahid Surakarta is using data collection methods that are divided into methods of observation, literature method,interview method.. System design method using object-oriented programming is using Unified Modeling Language (UML).